Marketing in and for a sustainable society - Malhotra, Naresh K. (Bingley, U.K. : Emerald, 2016)
This special issue will assemble a set of current, comprehensive/extended review articles/chapters written by distinguished experts on the state-of-the-art of marketing research and future prospects in the transition towards sustainable society. Reviews have been written for impact on marketing thought and clearly articulate the significance, and present critical perspectives and integrated theories on marketing for sustainability. This special issue features contributions from several top scholars including former editors of top journals in marketing.
Sustainability and marketing : concurrent pursuit of a smaller environmental footprint and a larger market footprint / Rajan Varadarajan -- Marketing's quest for environmental sustainability : persistent challenges and new perspectives / Jakki J. Mohr, Linda L. Price, Aric Rindfleisch -- A stakeholder marketing approach to sustainable business / Tracy L. Gonzalez-Padron, G. Tomas M. Hult, O.C. Ferrell -- Turning to sustainable business practices : a macromarketing perspective / Mark Peterson, Matt B. Lunde -- No through road : a critical examination of researcher assumptions and approaches to researching sustainability / Seonaidh McDonald, Caroline J. Oates, Panayiota J. Alevizou -- Toward pro-sustainability actions : a macro-behavioral perspective / Bipul Kumar, Nikhilesh Dholakia -- Reducing the attitude-behavior gap in sustainable consumption : a theoretical proposition and the American electric vehicle market / Diane M. Martin, Terhi Va<U+0308>isto<U+0308>.
Print version record
Keywords: Business & Economics -- Marketing -- General; Sales & marketing; Marketing; Sustainability